Potential economic benefits of BARI Gom 33: a blast-resistant bio-fortified wheat variety for Bangladesh - CGIAR Research Program on Wheat (2019)
Publication of study in peer-reviewed journal: part of a series of peer-reviewed journal articles addressing technologies and management practices to adapt and mitigate wheat blast in South Asia